Genetic Characterization of Didymella bryoniae Isolates Infecting Watermelon and Other Cucurbits in Florida and Georgia - Babu, Binoy (Plant disease, 2015)
Gummy stem blight caused by Didymella bryoniae (anamorph Phoma cucurbitacearum) is a major fungal disease of watermelon (Citrullus lanatus) and other cucurbits. Thirty-five isolates of Didymella and Phoma spp. associated with symptoms of gummy stem blight on watermelon, Canary melon (Cucumis melo), muskmelon (C. melo), and winter squash (Cucurbita maxima) from Florida and Georgia were characterized based on morphology on agar media, pathogenicity on 'Melody' watermelon, the internal transcribed spacer (ITS) sequence of ribosomal DNA (rDNA), random amplified polymorphic DNA (RAPD) analysis, and polymerase chain reaction (PCR) restriction fragment length polymorphism (RFLP) analysis. All of the isolates were pathogenic on watermelon but differed in virulence. RAPD and ITS sequence analysis indicated genetic variability among the isolates but PCR-RFLP analysis did not show any variability. ITS sequence phylogenetic analysis identified two isolates, DB-05 and DB-33, which had a greater identity to that of D. bryoniae isolates from China (98 to 100% sequence homology) than other isolates from Florida and Georgia (95 to 98%). These two isolates possessed a single nucleotide substitution of A to G at position 131 of the ITS1 region. The study characterized the genetic profile of a collection of D. bryoniae isolates from Florida and Georgia in relation to isolates from other U.S. states and countries